Medication Literacy for Pharmacists: A Review - Niken Nur Widyakusuma; Chairun Wiedyaningsih; Fivy Kurniawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The term health literacy has been emerging since the last decades. Poor health literacy had been realized as a main factor for poor health outcomes, higher medical costs, greater risk of death, and poor health status. With the health care system becoming increasingly complicated and the abundance of unclear health information, the ability to understand health information is important for the patients. Health literacy in the context of medicine was also being studied using different terms. It is rather difficult to compile when interventions to improve health literacy is in need of review. At the moment, the term “medication literacy” has been defined internationally by experts. With this definition, medication literacy studies will have the same concept and will be easier in benchmarking between studies. It is very important for pharmacists to recognize and assist patients with limited medication literacy. Although there are several barriers to do improvement in medication literacy, pharmacists can help both individually and through the system. Some of the interventions that can be carried out by pharmacists are assistance with drug information using literacy-sensitive techniques such as repetition, open questions, devices, demonstration on how to use drugs, and using printed materials to ensure patients understand their condition and treatment plans. Unfortunately, practicing pharmacists are lack of knowledge and even interest in medication literacy.